Three ages - Cline, Edward, 1892-1961; Keaton, Buster, 1895-1966; Cinetel Films ([United States] : Joseph M. Schenck Productions, 1923)
Men in three different ages (the Stone Age, the Roman Age, and the Modern Age) face off against a burly villain for love of a woman. --
Buster Keaton, Margaret Leahy, Wallace Beery, Joe Roberts, Lillian Lawrence, Blanche Payson, Horace Morgan, Lionel Belmore.
Photographed by William McGann and Elgin Lessley.
Silent, with English intertitles and musical accompaniment.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 15, 2015)
Keywords: Stone age -- Drama; Baseball -- Drama; Rome -- History -- Drama; Slapstick comedy films; Silent films; Feature films; Internet videos; Streaming video